STUDY OF ENVIRONMENTAL COMMUNICATION THEORY IN RESEARCH OF NATURAL RESOURCES MANAGEMENT - Heldi Yunan Ardian (Universitas Muhammadiyah Jakarta, 2019)
The recent environmental issues have become an important area of research for further review, especially on issues related to sustainability aspects that address environmental issues themselves, economic issues and social issues. The use of natural resources, particularly in relation to the field of agriculture, is considered a competition, which raises discourses that emerge beyond state boundaries and becomes a global discussion. Since communication is believed to provide a capable platform of facilitating the process of exchanging information, knowledge and wis- dom, this paper is expected to be the theoretical basis for research related to environmental issues and communica- tion to reach mutual understanding among the stakeholders involved. Theories offered include: environmental com- munication theory and stakeholder theory, supported: critical discourse analysis and stakeholder analysis as an ap- proriate method to answer the reseach question. Keywords: Environmental Communication, Discourse, Sustainability, Stakeholders